279. Dosimetric evaluation in O-arm spinal surgery procedures. (December 2018) - Ghetti, C.; Calabri, E.; Bianchi, M.G.; Piola, A.; Terroni, A.; Noukaoua, S. Mbakop; Giombelli, E.
Abstract : Purpose: The aim of this study was the evaluation of dose indexes for O-arm (Medtronic, USA)[1] volumetric scans used during spinal surgery procedures and a comparison with traditional diagnostic CT scans acquired before and/or after spinal surgery. Methods: The O-arm data set consists of 38 patients dose reports who underwent surgical vertebral stabilization (64 lumbar scans, 14 dorsal scans and 5cervical scans). Mean values for delivered mAs, CTDIvol and DLP were calculated for O-arm protocols. CT examinations used as benchmark were acquired on a Siemens Emotion 6 scanner and consist of 18 patients (12 dorsal-lumbar and 6cervical scans). The mean and 75 th percentile of CTDI/DLP distributions for lumbar, dorsal and cervical spine procedures were compared with the same dosimetric indexes obtained for CT examinations. Results: For O-arm lumbar scans (77% of total ), 7 protocols were used: 120 kV, 275(77–596) mAs, CTDIvol 24.1(6.8–52.3) mGy, DLP 386(109–837) mGycm. For dorsal scans 5 protocols were used: 120 kV, 200(62–469) mAs, CTDIvol 17.6(5.5–41.2) mGy, DLP 281(88–659) mGycm. For cervical scans 2 protocols were used: 120 kV, 68(38–98) mAs, CTDIvol 11(6.1–15.9) mGy, DLP 176(98–254) mGycm. The mean number of scans performed on O-arm for each patient was 2.2. The doses for O-Arm scans were lower than those for traditional CT examinations, with a reduction in lumbar area of −31, −55% for mean and 75th percentile of CTDIvol values and of −43, −59% for DLP; in dorsal area of −40, -59% for CTDIvol and of −50, −62% for DLP; in cervical area of −47, −15% for CTDIvol and −53, -50% for DLP. Conclusions: The O-arm system in spine surgery allows accuracy, lower rate of screw misplacement, reduced surgical time, less discomfort for patients and lower dose indexes values than traditional CT scans. These results are preliminary and we plan to increase our statistic.